The 100 simple secretsof Happy Families - David Niven (Harper One, 2004)
What do people with close families do differently than those with strained or unfulfilling family relationships? Psychological experts spend careers asking these questions. The answers these experts find are then chronicled and shared. . . with other experts. Taking advantage of more than a decade of the best scientific research the 100 Simple Secrets of Happy Families offers 100 practical pieces of advice on how people find and maintain love, joy and satisfaction in their family relationships. People don't have access to the journals and research reports that contain psychology's best advice on families and even if they did they would find these reports written in scientific jargon. That is, until now. In The 100 Simple Secrets of Happy Families each of the most important studies in the last ten years has been boiled down to its core finding and then expressed in a way everyone will understand. This advice is not based on one person's unique experiences, rather it reflects the research results of noted scientists studying the families of average Americans. Accompanying this research - based advice are real life stories that show the advice in action.